Bulgaria : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2000)
This paper assesses key aspects of Bulgaria's competitiveness. The behavior of a variety of a real exchange rate indicators and export performance is also examined in this study. The Balassa-Samuelson effect refers to the impact of differential productivity growth rates in the tradables and nontradables sectors on the real exchange rate. The following statistical data are also included in detail: total and private agricultural production, income accounts, labor force, employment and unemployment, monetary survey, foreign assets of the banking system, and so on.